Flexible work - Mohd Rosli, Nur Amalina; Ismail, Fadillah; Rashid, Umi Kartini; Salleh, Siti Hasliah; Kadir, Adibah Abdul (Penerbit Uthm, 2019)
Flexible working hours have as of late picked up a ton of consideration from associations and researchers as family-accommodating approach. These days, associations are attempting to fuse a culture of trust by offering representatives adaptability in the work environment (United Nation, 2010). Moreover, a few scientists contend that flexible working practices encourage work-life balance, and with moving family pattern such practices are beneficial for both women and men (Thomson, 2008; Pruyne, Powell & Parsons, 2012; Hofäcker & König, 2013). In this paper, connection between flexible working hours and work-life balance is inspected. This paper examines whether flexible working hours backing and improve work-life balance or on the other hand make challenges in adjusting among work and life jobs. Right off the bat, some past discoveries on flexible working hours are analysed. With the utilization of existing proof, adaptable working hours are considered from worker and boss sides so as to demonstrate that flexibility in the work environment gainful isn't just for employee, but for employer also. Besides, existing literature on work-life balance is filtered. Stress and representative prosperity are examined as they are two key results of work-life balance, one is negative and the other one is certain separately. The writing comes up short on the proof of flexible working hours affecting on work-life balance; nonetheless, two ideas are regularly utilized together in the investigations. The section continues with a concise talk on a picked point. Lastly, conclusion is given to condense the thoughts of the section.